DIALLEL ANALYSIS OF RESISTANCE TO BACTERIAL STALK ROT (Pectobacterium chrysanthemi pv. zeae Burk., McFad. and Dim.) IN CORN (Zea mays L.) - Subekti, Nuning A.; Salazar, Artemio M. (Indonesian Journal of Agricultural Science, 2007)
One of the major disease problems affecting maize farming inthe Philippines is bacterial stalk rot (BSR) caused by Pectobacteriumchrysanthemi pv. zeae Burk., McFad. and Dim., whichis formerly known as Erwinia chrysanthemi. The annual lossdue to BSR is estimated at PhP. 20 million equivalent to Rp3.5billion. At present, there is no effective control method againstBSR and, therefore, varietal improvement through breedingresistant germplasms is needed. The present study aimed todetermine the combining ability and the extent of additive andnon-additive genetic effects in corn inbred lines with a rangeof reaction to BSR. Four resistant lines (S3YB 137-1-1-B, TUPI(S3) 5-1-B, TUPI (S3) 15-2-B, and 97-835) and two susceptiblelines (CML 295 and 97-733) were used as genetic materials.Generation of test entries and evaluation of disease resistancewere conducted at the experimental farm station of Universityof the Philippines Los Banos and Institute of Plant BreedingLos Banos, respectively, during 2002 to 2003 wet seasons.Griffingâs diallel mating system Model 1, Method 1 was followedin generating the test entries to make a total of 36 entries (sixselfed parental lines and 15 each of F1 crosses and their reciprocalcrosses). The entries were then evaluated for diseaseresistance in a yield trial following a randomized complete blockdesign (RCBD) with two replications. Results of diallel analysisshowed two lines, S3YB 137-1-1-B and TUPI (S3) 5-1-B,exhibited the best general combining ability (GCA) for resistanceto BSR, while the crosses S3YB 137-1-1-B x TUPI (S3)5-1-B and TUPI (S3) 5-1-B x 97-835 performed the bestspecific combining ability (SCA) for the resistance. GCA effectwas greater than that of SCA. This indicated that additive geneeffects were found to be more important than non-additive geneeffects in the expression of resistance to BSR in the six cornlines used. Therefore, breeding programs towards recurrentselection that emphasize GCA would be more appropriate forBSR resistance improvement involving those six lines.